2021
DOI: 10.1364/oe.422060
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of dispersive waves emission via quadratic spectral phase

Abstract: We investigate the process of dispersive waves (DWs) emitted from Gaussian pulse (GP) with an initial quadratic spectral phase (QSP). We show that the radiation of DWs is strongly affected by the QSP parameter. The conversion efficiency and resonant frequency of DWs are effectively enhanced and controlled by tuning the sign and magnitude of the initial QSP. At variance with the case of pure GP, the DWs emission is first advanced and then delayed for negatively QSP modulated GPs; while it is always delayed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Quadratic, cubic, sinusoidal, step, and triangular spectral phase modulations have been exploited for realizing a variety of novel shaped pulses. [21][22][23][24] More recently, Lourdesamy et al utilized spectral pulse shaper to generate a pulse train with smooth soliton-like envelope for enhancing nonlinear effects. [25] Among these phase modulation patterns, sinusoidally spectral phase (SSP) exhibits unique characteristics because of its periodic modulation with adjustable modulation frequency and depth as well as absolute phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quadratic, cubic, sinusoidal, step, and triangular spectral phase modulations have been exploited for realizing a variety of novel shaped pulses. [21][22][23][24] More recently, Lourdesamy et al utilized spectral pulse shaper to generate a pulse train with smooth soliton-like envelope for enhancing nonlinear effects. [25] Among these phase modulation patterns, sinusoidally spectral phase (SSP) exhibits unique characteristics because of its periodic modulation with adjustable modulation frequency and depth as well as absolute phase.…”
Section: Introductionmentioning
confidence: 99%
“…Quadratic, cubic, sinusoidal, step, and triangular spectral phase modulations have been exploited for realizing a variety of novel shaped pulses. [ 21–24 ] More recently, Lourdesamy et al. utilized spectral pulse shaper to generate a pulse train with smooth soliton‐like envelope for enhancing nonlinear effects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we call it "Cherenkov radiation" [24,25] or "non-soliton radiation" [26]. Researchers have found that dispersive waves can be manipulated by quadratic spectral phases [27], sinusoidal phases [28] and modulation high-order effects [29].…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] More recently, the temporal structure of pump pulse has also been extended from symmetric to asymmetric to control the resonant radiation, including dark and Peregrine soliton, [31,32] multimode and shock waves, [33,34] and self-accelerating pulse. [35,36] In our previous works, we have reported that the conversion efficiency and radiation frequency of DWs can be controlled by adjusting the spectral phase modulation, [37,38] which makes the shaped pulses with symmetrical spectral shapes, while their temporal profiles exhibit asymmetric structure. In particular, the asymmetric temporal structure of the shaped pulse can trigger temporal collisions that can significantly alter the intensity and shape of the resonance spectrum.…”
Section: Introductionmentioning
confidence: 99%